Avaliação de efeitos toxicológicos e comportamentais de Panax ginseng C.A. Meyer em ratos - Matos, Ana Laura de Souza Almeida (2013)
Panax ginseng CA Meyer (Araliaceae) is a herbaceous plant widely used in China, South Korea, Japan and other Asian countries for the treatment of various diseases micro circulatory, cerebrovascular, among others, representing one of the drugs used by older man. It has over 30 biologically active ginsenosides with different pharmacological and behavioral effects and inhibitory effect on the NMDA receptor. The amino acid glycine is a co-agonist of the NMDA receptor, activating this receptor. At the cellular level, ketamine is widely known to be NMDA receptor antagonist. The aim of this study was to evaluate the general activity in the open field, and anxiety in elevated plus maze, mice treated with P. ginseng compared with the action of ketamine and glycine, to better understand the action of this herbal medicine at the NMDA receptor. We used 66 adult male rats were divided into six groups: a positive control, treated for 30 days with water by gavage, who received glycine (500mg/kg; po) on days 7, 14, 21 and 28 of treatment, one hour before of behavioral assessment, a negative control was treated for 30 days with water by gavage received ketamine (5mg/kg, ip) on days 7, 14, 21 and 28 of treatment, one hour prior to behavioral evaluation, three experimental groups, receiving 100, 200 or 300 mg / kg P. ginseng by gavage for 30 days and one group treated solely with white water, and is also administered 1 ml of water by gavage one hour prior to behavioral evaluation. Animal behavior in these three groups was also examined on days 7, 14, 21 and 28 of treatment. On day 30 of treatment, the animals were anesthetized with thiopental (70mg/kg) for blood collection and after euthanasia, withdrawal of various organs. There were no changes in weight and body weight gain and weight reasons in organ / body weight. However the consumption of water and food values showed a significant increase. Serum levels of AST was increased in a dose-dependently in the animals treated with doses of P. ginseng, glycine and ketamine as compared to the blank group. Unlike creatinine levels proved to be decreased in all treated groups when compared with white. However, the level of urea in these groups was reduced and no changes were observed in the ALT parameter. Histopathological examination revealed no changes in cell morphology in different tissues. There were no behavioral changes in the elevated plus maze and few changes were observed in the open field, animals treated with P. ginseng, glycine and ketamine when compared to white. These data suggest that the doses of P. ginseng employed were unable to induce general toxicity in rats treated for 30 days and also shows that the general behavior of mice treated with P. ginseng was slightly different from that observed in animals treated with ketamine and glycine. Finally, the study on the elevated plus maze showed that the extract of P. ginseng showed no anxiolytic or anxiogenic action